Forging a Symbiotic Synergy Between Academia & Industry - Taganas, Rey Antonio (Kajian Manajemen dan Bisnis, 2010)
Universities and industry have engaged in a variety of productive relationships that have provided benefit to universities through expanded research and consultancy projects, curriculum development, job opportunities for undergraduate students, and additional revenue that can support the academic mission. Industry, on the other hand, has benefited through specialized education programs, the ability to work with faculty with expertise in a specialized field of research, and access to innovative ideas that can enhance product development and improve corporate strategy. The author illustrates this by presenting a case study of the University of Asia & the Pacific (UA & P),a university in Manila,Philippine which has successfully promoted a symbiotic synergy between their institution and the Philippine business community.